Prenatal diagnosis of congenital megalourethra: case report and literature review - Öztürk, Filiz Halıcı; Türkmen, Gülenay Gençosmanoğlu; Ergun, Elif; Tiryaki, H Tuğrul; Şahin, Dilek (The Turkish Journal of Pediatrics, 2022)
Background. Congenital megalourethra is an uncommon cause of lower urinary tract obstruction that is rarely prenatally diagnosed in second trimester sonographic examination as a cystic genital mass. Case. In the presented case, the megalourethra was accompanied with bilateral mild pelviectasis. The newborn had no morbidity during follow-up period. To review the literature, electronic databases including PubMed, Web of Science and Google Scholar were searched up to February 15, 2021. In 51 prenatally diagnosed cases in the literature, most of the cases had accompanying congenital anomalies, especially structural abnormalities in the genitourinary. Conclusions. In the absence of associated abnormalities, the condition of the upper urinary tract is the main determinant of postnatal outcome. The outcome of congenital megalourethra may be good as in our case, but there may also be serious disorders such as renal failure, pulmonary hypoplasia, erectile dysfunction and fertility issues.
Keywords: congenital megalourethra; lower urinary tract obstruction; obstructive uropathy; prenatal diagnosis; prenatal sonography